Students' Experiences in Developing English Skills for Post-Study Career Readiness: An Interpretative Phenomenological Study - Dwi Tatalia; Ella Masita; Fortunasari Fortunasari; Hadiyanto Hadiyanto (FKIP - Universitas Riau, 2026)
English proficiency is increasingly important for graduate employability, yet formal university learning does not always prepare students for spontaneous professional communication. This study explored how master's students in English Education experience the development of English skills for Post-Study Career Readiness. A qualitative design using Interpretative Phenomenological Analysis was employed. Three participants were selected purposively from an English Education master's program at Universitas Jambi, and data were generated through in-depth semi-structured interviews. The analysis identified four interconnected challenges: persistent language anxiety in high-stakes situations, a gap between academic English and professional communication demands, limited access to authentic English practice, and declining motivation caused by perceived unpreparedness. These experiences show that career-related English development is shaped not only by linguistic competence but also by professional identity, opportunities for authentic interaction, and students' confidence in approaching future work roles. The study concludes that English Education programs should provide more professionally contextualized communication practice, authentic workplace exposure, and affective support so that students can connect academic learning with realistic career demands.